2014
DOI: 10.5114/aoms.2014.40642
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cough – assessment of treatment efficacy based on two questionnaires

Abstract: IntroductionEfficacy of chronic cough treatment is ambiguous. The aim of the study was to analyze chronic cough alleviation after specific treatment and the relationship between cough etiology and treatment efficacy.Material and methodsA stepwise diagnostic approach was used to diagnose cough etiology in non-smoking adults with chronic cough. In all patients specific treatment was applied. Two different questionnaires – a visual analog scale and a 5-degree scale – were used to assess cough severity before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
9
0
2
Order By: Relevance
“…With respect to chronic cough, although all studies were prospective and none mentioned any harms, 11 studies met our criteria for quality assessment and all had a high risk of bias (Table 4). [18][19][20][21][22][23][24][25][26][27][28] Although 10 were prospective studies, none mentioned any harms. Although six used a validated cough outcome tool, none had a control group.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to chronic cough, although all studies were prospective and none mentioned any harms, 11 studies met our criteria for quality assessment and all had a high risk of bias (Table 4). [18][19][20][21][22][23][24][25][26][27][28] Although 10 were prospective studies, none mentioned any harms. Although six used a validated cough outcome tool, none had a control group.…”
Section: Resultsmentioning
confidence: 99%
“…Asthma is a common disease of children and is one of the most common causes of chronic cough in adult non-smokers, characterized by the presence of increased numbers of activated mast cells and eosinophils in the airway [ 1 , 2 ]. In addition to the presence of inflammatory cells in the airway, the airways demonstrate varying levels of structural changes termed airway remodeling [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effective therapies for CC are one of the most important unmet needs in respiratory diseases. The effectiveness of CC management, however, is highly unsatisfactory [3,11,12]. In the study by Haque et al [3] 42% of patients with CC did not improve despite causal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that only 55% of patients with CC reported significant decrease in cough severity as a result of applied therapy [11]. Similarly, in the recently published survey study approximately 36% of patients with CC declared no effect of cough therapy [12]. According to the ACCP guidelines, persistent untreatable cough refers to 5-10% of all CC patients undergoing treatment and up to 46% of patients managed in specialised cough clinics [4].…”
Section: Discussionmentioning
confidence: 99%